2017
DOI: 10.1097/mbc.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation is more affected by quick than slow bleeding in patients with massive blood loss

Abstract: Profuse blood loss affects blood coagulation to various degrees. However, whether bleeding speed affects coagulation remains uncertain. This study aimed to evaluate the effect of bleeding speed on coagulation function. A total of 141 patients in the Department of Thoracic Surgery of our hospital were evaluated between January 2007 and February 2014. There are two groups of patients, those who received decortication for chronic encapsulated empyema were called the slow-bleeding group, and those who received tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Studies have shown that massive bleeding can cause the loss of a large amount of blood-clotting factor and platelets, causing the coagulation function to decrease, especially in those with an acute condition [19]. Consistently, our studies reported that the INR and PT of severe patients were statistically higher than in mild patients.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that massive bleeding can cause the loss of a large amount of blood-clotting factor and platelets, causing the coagulation function to decrease, especially in those with an acute condition [19]. Consistently, our studies reported that the INR and PT of severe patients were statistically higher than in mild patients.…”
Section: Discussionsupporting
confidence: 89%
“…But plasma levels of tPA can also increase in situations of acute stress due to its release from the Weibel-Palade bodies of the endothelium. 26 Thrombin, epinephrine, vasopressin, desmopressin, bradykinin, and other substances trigger the release of tPA. Therefore, initially, with high basal levels of plasminogen, the fibrinolysis pathway is relatively well preserved during the early stages of hemodilution.…”
Section: Consequences Of Hemodilutionmentioning
confidence: 99%
“…25 For example, it has been reported that the activity of antithrombin can decrease to levels of 30% after a 1:6 dilution of whole blood with normal saline in vitro. 17,26 Decreased antithrombin activity prolongs the half-lives of thrombin and FXa, thereby potentially contributing to improved hemostasis in this state of hypocoagulability secondary to hemodilution. However, excess activity of thrombin and activated FX in the circulation could contribute to the pathogenesis of trauma surgery-induced coagulopathy, disseminated intravascular coagulation, and also to postoperative deep vein thrombosis.…”
Section: Consequences Of Hemodilutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbs that alter such equilibrium may result in hemorrhage or thrombosis, while the latter is one of the most important cardiovascular diseases, as ischemic attack, stroke and myocardial infarction. They lead to mortality or morbidity worldwide, mainly in western populations (Zhao et al, 2017). Thrombosis generally has medical complications to patients or recurrent hospitalization, and this fact increases healthcare costs (Furie and Furie, 2008).…”
Section: Introductionmentioning
confidence: 99%